Peningkatan Kesadaran Lingkungan Melalui Aksi Bersih Pantai di Pulau Panjang Bangka Tengah - Rema , Dareen Nadya; Selvika, Zerli; Harahap, Apriliyani; Kurniawan, Kurniawan; Saputra, Denny; Ulum, Miftahul; Priyambada, Agung; Notonegoro, Hartoyo; Wulan, Retno (Apik Cahaya Ilmu, 2025)
This activity addresses coastal environmental issues and promotes the sustainable management of fisheries and marine tourism. The program involved 40 students with a theoretical and practical approach. The practical component, a beach clean-up, successfully collected around 15 sacks of waste, predominantly plastic. Participants also engaged in snorkeling to directly observe the marine ecosystem. In addition, the Focus Group Discussion (FGD) recommended community empowerment, integration of waste management and tourism development, and participatory zoning. This program aims to foster environmental awareness and strengthen collaboration among stakeholders to ensure the sustainable management of coastal resources in Bangka Belitung.